Knowledge and Practices Assessment of Decontamination during Root Canal Treatment in Saudi Arabia - Necdet Adanir; Hassan Alkhalaf; Maram H. Alanazi; Asma S. Alghamdi; Abdullah A. Aljami; Amjad O. Aljohani; Khames T. Alzahrani (International Journal of Innovative Research in Medical Science, 2021)
Introduction: Bacteria play a crucial role in the pathogenesis of pulpal and periradicular pathoses. For example: Apical periodontitis is an inflammation of dental periapical tissues developed as a response to colonization of microorganisms in root canal system. The elimination of microbial species from the infected root canal system necessitates a strict aseptic condition for Instrumentation, disinfection and inter appointment medication. Enterococcus faecalis and Candida albicans had been commonly associated organisms in treatment-resistant infections. Methods: This was an observational cross-sectional study based on web-survey questionnaires developed by the authors with high confidence. The sample size was 304 estimated using the Qualtrics calculator with a confidence level of 95% and a margin of error of 5%. The questionnaire is divided into sections, regarding endodontic practice include endodontic education , years of experience , used of rubber dam or no and how to used irrigant solution whoever Sodium hypochlorite (NaOCl), Chlorhexidine, chelating agents (EDTA) or (MTAD) and reasons of every irrigant that prevents during root canal treatment. Data were collected using Google forms and prepared for analysis using Microsoft Excel. Statistical analysis was performed using the SPSS software. Results: A total of 304 participants responded, 44.1% dental interns, 39.5% General Dentist, 9.9% Endodontist, 6.3% other dental specialty. the Probable reasons that prevent them using rubber dam during root canal treatment are: 5.9% due to difficulty to apply, 9.2% due to lack of materials, 5.3% because it is a time-consuming, 1.6% said that other isolation methods are enough (partial isolation), 3.9% because of multiple reason combined together. 48.7% they always use rubber dam, so they did not choose any of the previous reasons. Conclusion: In conclusion, we identify and understand, most of the participants “always using rubber dam” during root canal treatment and the most common reasons was time consumption that prevented dentist from using rubber. In this study majority of participants preferred NaOCl 81.9% and 7.1% don’t use it.